Dataset of the de novo assembly and annotation of the marbled crayfish and the noble crayfish hepatopancreas transcriptomes - Ljudevit Luka Boštjančić; Caterina Francesconi; Christelle Rutz; Lucien Hoffbeck; Laetitia Poidevin; Arnaud Kress; Japo Jussila; Jenny Makkonen; Barbara Feldmeyer; Miklós Bálint; Klaus Schwenk; Odile Lecompte; et al. (BMC Research Notes, 2022)
Abstract Objectives Crayfish plague disease, caused by the oomycete pathogen Aphanomyces astaci represents one of the greatest risks for the biodiversity of the freshwater crayfish. This data article covers the de novo transcriptome assembly and annotation data of the noble crayfish and the marbled crayfish challenged with Ap. astaci. Following the controlled infection experiment (Francesconi et al. in Front Ecol Evol, 2021, https://doi.org/10.3389/fevo.2021.647037 ), we conducted a differential gene expression analysis described in (Boštjančić et al. in BMC Genom, 2022, https://doi.org/10.1186/s12864-022-08571-z ) Data description In total, 25 noble crayfish and 30 marbled crayfish were selected. Hepatopancreas tissue was isolated, followed by RNA sequencing using the Illumina NovaSeq 6000 platform. Raw data was checked for quality with FastQC, adapter and quality trimming were conducted using Trimmomatic followed by de novo assembly with Trinity. Assembly quality was assessed with BUSCO, at 93.30% and 93.98% completeness for the noble crayfish and the marbled crayfish, respectively. Transcripts were annotated using the Dammit! pipeline and assigned to KEGG pathways. Respective transcriptome and raw datasets may be reused as the reference transcriptome assemblies for future expression studies.